Plastic deformation of synthetic quartz nanopillars by nanoindentation for multi-scale and multi-level security artefact metrics - Shunya Ito (Nature Portfolio, 2021)
Abstract Individual authentication using artefact metrics has received increasing attention, as greater importance has been placed on the security of individual information. These artefact metrics must satisfy the requirements of individuality, measurement stability, durability, and clone resistance, in addition to possessing unique physical features. In this study, we proposed that nanostructures of synthetic quartz (SQ) deposited on an SQ plate may provide sophisticated artefact metrics if morphological changes could be intentionally introduced into the SQ nanostructures at certain positions. We fabricated SQ nanopillars using a mass-production method (ultraviolet nanoimprint lithography) and investigated their mechanical deformation using nanoindentation with a spheroid diamond tip through a loading and unloading cycle. The SQ nanopillars with an aspect ratio of 1 (i.e., diameters D of 100 and 200 nm with corresponding heights H of 100 and 200 nm, respectively) could be plastically deformed without collapsing within a specified pillar-array format at programmed positions. The plastically deformed SQ nanopillar arrays demonstrated multi-scale (sub-millimetre, micrometre, and nanometre) and multi-level (shape, area, diameter, and height) individuality authentication and clone resistance. Because SQ is physically and chemically stable and durable, individuality authentication can be a highly reliable tool on Earth and in space.